Health problems caused by Temporomandibular Dysfunction (TMD) and their possible forms of treatment (Research, Society and Development, 2024)
Objective: To discuss TMD, addressing what this dysfunction can cause, how it occurs, and what problems and solutions are applied to this condition. Methodology: Searches using the website databases: The Cochrane Library, Web of Science, PROSPERO, Science Direct, CAPES Journal Portal, Scielo, Research, Society and Development and Google Academy. As this article is a narrative literature review, the study of Rother was used to serve as a basis for structuring the article. Results: Our search resulted in 40 articles. Conclusion: TMD is a dysfunction of the temporomandibular joint that can be caused by emotional problems such as anxiety, due to changes in the oral structure, with the occlusal splint as a possible treatment. Problems such as changes in the posture of the cervical spine can cause TMD, and butolinic toxin is a possible treatment for this dysfunction, which can also cause hearing problems if there is no improvement.